Connexions : Histories of Race and Sex in North America - Morgan, Jennifer L. (Jennifer Lyle); Downs, Jim, 1973-; Brier, Jennifer (Book collections on Project MUSE., 2016)
"Connexions investigates the ways in which race and sex intersect, overlap, and inform each other in United States history. An expert team of editors curates thought-provoking articles that explore how to view the American past through the lens of race and sexuality studies. Chapters range from the prerevolutionary era to today to grapple with an array of captivating issues: how descriptions of bodies shaped colonial Americans' understandings of race and sex; same-sex sexual desire and violence within slavery; whiteness in gay and lesbian history; college women's agitation against heterosexual norms in the 1940s and 1950s; the ways society used sexualized bodies to sculpt ideas of race and racial beauty; how Mexican silent film icon Ramon Navarro masked his homosexuality with his racial identity; and sexual representation in mid-twentieth-century black print pop culture. The result is both an enlightening foray into ignored areas and an elucidation of new perspectives that challenge us to reevaluate what we 'know' of our own history. Contributors: Sharon Block, Susan K. Cahn, Stephanie M.H. Camp, J.B. Carter, Ernesto Chavez, Brian Connolly, Jim Downs, Marisa J. Fuentes, Leisa D. Meyer, Wanda S. Pillow, Marc Stein, and Deborah Gray White"--